EXPLORING STUDENTS’ PERSPECTIVES OF ENGAGEMENT ON AN INDOOR EXPLORACE ACTIVITY IN ESL CLASSROOM: Received: 24th Abstract 2025, Revised: 7th May 2025, Accepted: 26th May 2025, Date of Publication: 11th November 2025 - Suhaily Abdullah, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In the post-COVID era, the integration of digital tools in English Language Teaching (ELT) has become increasingly important for promoting interactive and engaging classroom activities. This study investigates the use of Prezi (online platform) in an indoor language game called Explore-Hunt, to enhance student engagement in learning. Using the ASPECT (Assessing Student Perspective of Engagement in an Active-Learning Classroom) framework (Wiggins et al., 2017), the research aims to gather feedbacks from 48 diploma students across two different courses, selected through purposive sampling. Descriptive statistical analysis revealed high engagement across all three ASPECT constructs: Value of Activity (M = 4.81, SD = 0.49), Personal Effort (M = 4.86, SD = 0.46), and Instructor Contribution (M = 4.96, SD = 0.23). The findings highlight the effectiveness of incorporating digital tools and gamification in creating dynamic and interactive learning environments, particularly in TVET ESL education context. The study also contributes to the growing body of research on the application of the ASPECT framework in classroom action research, highlighting the potential for broader adoption of similar active learning strategies. Future research could explore scaling or adapting these methods for use in other ESL and subject-specific classroom.